Bone and Flesh, Death and Life: Representing the Human Body in Anil's Ghost - TURAN, AYŞEGÜL (My University, 2019)
Michael Ondaatje’s Anil’s Ghost portrays the events evolving around Anil Tissera, a forensic anthropologist who, after living in England and the US for fifteen years, returns to her homeland Sri Lanka as part of an international human rights group to help with the investigation of mass murders. Anil and Sarath, a local archaeologist, are to identify the victims of unknown extrajudicial executions, which proves difficult and dangerous in the volatile and violent atmosphere of Sri Lanka as represented by the discovery of a recently buried skeleton in an ancient burial site controlled by the army. In this paper, I will focus on the depictions of the body, specifically those of skeletons and bones, to examine the novel’s metonymic representation of the individual and collective memory. As the violence of civil war becomes etched onto human bodies, bones start to serve as a repository of cultural memory after death. In the novel, “Sailor,” the recently buried skeleton, stands for all those bodies that have disappeared under not-so-mysterious circumstances. In other words, the attempt to give the Sailor a name and a face becomes emblematic of the desire to acknowledge the loss and suffering as well as honoring the dead. I contend that in the novel, the conscious effort to strip the bodies of their identity and to anonymize them does not lead to their ultimate erasure from history; on the contrary they, through the lifeless bones, draw attention to this attempt and hence become an essential part of cultural memory.